ACO AND NON-ACO AFFILIATED HOSPITALS DISCHARGE PATTERN TO SNFS BASED ON SNFS STAR RATING. (11th November 2018) - Ferdows, N B; Rahman, M; Mor, V
Abstract: The Medicare Accountable Care Organization (ACO) programs encourage a stronger relationship between hospitals and Skilled Nursing Facilities (SNFs). We examine whether ACO-affiliated hospitals discharge their patients to higher quality SNFs compared to other hospitals using a 20 percent random sample of beneficiaries discharged to a SNF following an acute care hospitalization during 2008–2015. We use measures of proximity between the patient's home and each SNF and from SNF to hospital as instruments to control for potential bias in choosing SNFs. We found a general increase in the quality of skilled nursing facilities and an overall increase in the percent of patients sent to higher quality SNFs over time. The ACO- affiliated hospitals, however, could send their patients to slightly higher star-rating SNFs compared to non-ACO hospitals. Higher improved performance quality in the most recent years for the pioneer-ACO hospitals indicate that the impact of ACOs on quality is developing.